QUALIDADE DE VIDA E BEM-ESTAR SUBJETIVO EM IDOSOS INCLUÍDOS EM PROGRAMA DE CULTURA, EDUCAÇÃO E PROMOÇÃO DA SAÚDE - VENTURA, CRISTINA DE FÁTIMA (2021)
The objective of this study was to identify, describe and analyze the Quality of Life and Subjective Well-Being of the elderly, through the eyes of the aging person. The theoretical perspective Lifespan, which brings the development paradigm throughout the course of life, was the basis of the theoretical foundation. The research is characterized by a descriptive cross-sectional study with a quantitative approach, carried out with 80 elderly people aged 60 and over, of both sexes, included in an education, culture and health promotion program, in the municipality of Bertioga. The following instruments were used: a) Sociodemographic Qualification Questionnaire; b) Quality of Life Scales of international recognition (WHOQOL -Bref and WHOQOL -Old), important to know the perceptions of the population, especially the elderly; c) Welfare Scale – Subjective (Albuquerque & Tróccoli). Data were compiled using SPSS software version 22 for Windows using the ANOVA test to compare the means between the variables and Pearson’s correlation, with p values <0.05 being accepted as statistically significant. The results obtained confirmed the hypothesis that the sociodemographic variables, sex, education, marital status and work condition, for the group in question, are not related to a better perception of quality of life and subjective well-being, as well as age is significant in terms of the perception of these constructs. However, a significant difference was observed (p <0.05) for three situations: a) singles and widowers have more negative affect and separated and divorced older people have less influence, b) men have more positive affect than women and c) the participants who are active in the labor market have a significant relationship with the Intimacy facet, which concerns the perception of the feeling of companionship and greater availability to love and be loved. Comparing the findings of this research with studies in the elderly population not included in programs for the elderly, it is concluded that elderly people who participate in organized collective activities have a better perception of quality of life and subjective well-being.